Food safety and value chain coordination in the context of a transition economy: The role of agricultural cooperatives - Drini Imami; Vladislav Valentinov; Engjell Skreli (International Journal of the Commons, 2021)
In Albania development gaps in the area of food safety are calling for stronger vertical coordination within the agrifood value chains. The paper explores the possibility of vertical coordination being strengthened through the development of agricultural cooperatives and informal farmer groups. In two reported case studies, these organizations have been shown to be called into life by the need to advance vertical coordination. Moreover, the case studies reveal that downstream agribusiness agents, who normally oppose farmers' countervailing power, promote, support, and even initiate cooperatives and farmer groups, in order to implement food safety standards. The emerging cooperation among farmers not only enhances their participation in the value chain but also generates mutual trust.
Keywords: 330; cooperatives; food safety standards; social capital